Strategic Investment Decision Analysis for Hydrogen Supply Alternatives at PT Energi Nasional X - Amar Ma’ruf; Pri Hermawan (Riviera Publishing, 2026)
This study aimed to identify feasible hydrogen supply alternatives and determine the most suitable strategic option for PT Energi Nasional X. To achieve this objective, the research employed an integrated analytical framework consisting of SWOT–TOWS analysis, the Fuzzy Delphi Method (FDM), and the Analytic Hierarchy Process (AHP). SWOT–TOWS analysis was used to identify internal strengths and weaknesses as well as external opportunities and threats, which were then translated into feasible strategic alternatives. The FDM was applied to validate the relevance of evaluation criteria and obtain expert consensus from subject matter experts (SMEs). Finally, AHP was used as the primary multi-criteria decision-making method to determine criteria weights, evaluate alternatives through pairwise comparisons, and generate a final ranking of alternatives in a structured and consistent manner. The FDM analysis validated eight main evaluation criteria, namely capital expenditure (CAPEX), operating expenditure (OPEX), net present value (NPV), equipment reliability, supply continuity, H? quality/purity assurance, implementation risk, and operability and maintainability. The AHP results indicated that equipment reliability, net present value (NPV), and supply continuity were the most influential criteria in determining the preferred hydrogen supply strategy. The final AHP ranking showed that the New Plant alternative achieved the highest global priority score compared with the Revitalization and External Procurement alternatives. Although the New Plant option required the highest initial investment cost, it provided superior long-term operational reliability, stronger supply continuity, better process control, and improved operational independence from external suppliers. A sensitivity analysis was also conducted to evaluate the robustness of the decision model under various weighting scenarios. The results showed that the ranking of alternatives remained stable despite changes in criteria weights, indicating that the decision model is robust and reliable for supporting strategic investment decisions. Based on the overall analysis, this study concluded that the development of a new hydrogen plant is the most appropriate and sustainable hydrogen supply strategy for PT Energi Nasional X. The selected alternative offers the best balance between financial value, operational reliability, risk management, and long-term business sustainability, while supporting continuous polypropylene production and strengthening the competitiveness of PT ONE ENERGY.